Longitudinal change in regional brain volumes in prodromal Huntington disease. Issue 4 (30th September 2010) - Aylward, Elizabeth H; Nopoulos, Peggy C; Ross, Christopher A; Langbehn, Douglas R; Pierson, Ronald K; Mills, James A; Johnson, Hans J; Magnotta, Vincent A; Juhl, Andrew R; Paulsen, Jane S; ,
Abstract : Objective: As therapeutics are being developed to target the underlying neuropathology of Huntington disease, interest is increasing in methodologies for conducting clinical trials in the prodromal phase. This study was designed to examine the potential utility of structural MRI measures as outcome measures for such trials. Methods: Data are presented from 211 prodromal individuals and 60 controls, scanned both at baseline and at the 2-year follow-up. Prodromal participants were divided into groups based on proximity to estimated onset of diagnosable clinical disease: far (>15 years from estimated onset), mid (9–15 years) and near (<9 years). Volumetric measurements of caudate, putamen, total striatum, globus pallidus, thalamus, total grey and white matter and cerebrospinal fluid were performed. Results: All prodromal groups showed a faster rate of atrophy than controls in striatum, total brain and cerebral white matter (especially in the frontal lobe). Neither prodromal participants nor controls showed any significant longitudinal change in cortex (either total cortical grey or within individual lobes). When normal age-related atrophy (ie, change observed in the control group) was taken into account, there was more statistically significant disease-related atrophy in white matter than in striatum. Conclusion: Measures of volume change in striatum and white-matter volume, particularly in the frontal lobe, may serve as excellent outcome measures for future clinical trials in prodromal Huntington disease. Clinical trials using white matter or striatal volume change as an outcome measure will be most efficient if the sample is restricted to individuals who are within 15 years of estimated onset of diagnosable disease.